An investigation on synthesis, aggregation, and mechanical properties of Al 6082 nanocomposites reinforced by Titanium carbide. (2022) - Lal Rinawa, Moti; Chauhan, Prashant; Kumar Sharma, Amit; Kumar Singh, Hari; Ankit; Karuna, M.S.; Sudhakar, M.
Abstract: Composites of nanostructured Al 6082 and TiC (1, 1.5, 2 and 2.5 wt%) were formed by milling of about 35 h and mechanical alloying. Cold uniaxial compaction was used to solidify the milled particles, and various temperatures of sintering followed (698, 748 and 798 K). Differential thermal examination of the nanocomposite powders revealed their an Al 6082 matrix with a homogeneous dispersion and scattering. Compressive strength and hardness were analyzed for their mechanical qualities. The Al 6082 – 2.5 wt% TiC nanocomposite sintered at 798 K had a maximum hardness of 1265 MPA, which was roughly four times as high as the Al 6082 microcrystalline material's maximum hardness. When 2 wt% TiC was applied, the green compressive strength reached 237 MPA. There has been research done on the influence of densification on the compaction stiffness, impact strength and Vickers hardness reinforced with carbon nanotube fibres. Nanocomposite powders' compressibility was also analyzed by using the Heckel, Panelli, and Ambrosio Filho and Ge equations.